Peningkatan Kompetensi Mahasiswa melalui Pembekalan Kuliah Kerja Nyata Tematik Wira Desa (KKNT-WD) - Muniarty, Puji; Wulandari, Wulandari; Saputri, Della (Dharma: Jurnal Pengabdian Masyarakat, 2021)
Higher Education is an educational unit that organizes Higher Education. Universities are required to carry out the tridharma which consists of teaching, research and community service. Community service carried out by students in the form of Real Work Lectures (KKN) is a form of implementing collaborative student learning experiences through the implementation of theory and practice that will be applied to problems found in the village so that efficient, effective and appropriate solutions and strategies can be determined to improve the economic well-being of the community. However, to carry out the Wira Desa Thematic Real Work Lecture (KKNT-WD) which has been determined by the Bima College of Economics (STIE), students who have passed the KKN registration administration must attend the KKNT-WD debriefing in order to improve knowledge competence before interacting with the community and knowing village potential for the preparation of work programs during activities at the KKN location. The form of debriefing for KKNT-WD is carried out face-to-face, lectures and questions and answers. The result of the debriefing is that students know and understand the general description and concept of the Wira Desa Real Work Lecture and its outputs in the form of publications in community service journals published online.